Creating water sensitive places in Hangberg - Smith Mari (School of Architecture, Planning and Geomatics, 2024)
The neighbourhood of Hangberg has had a long and intimate relationship with water, the neighbourhood is located around the Hout Bay harbour where the fishing industry provides the main source of employment and residents depend on clean water for their daily needs. This relationship has however been put under strain as urban development has affected the natural and urban water cycle resulting in flooding, soil erosion, pollution and water shortages. Urban spaces and residents have become detached from water as infrastructure tends to be hidden underground and water is seen as a nuisance rather than an asset. Even though we depend on water resources, it is often not a priority in the design and development of our urban spaces. We need to relook at the relationship between water and urban space to provide a solution that integrates the urban water cycle with good qualities of urban design to create a liveable neighbourhood